Best Paper Selection (Yearbook of Medical Informatics, 2021)
Bell SK, Delbanco T, Elmore JG, Fitzgerald PS, Fossa A, Harcourt K, Leveille SG, Payne TH, Stametz RA, Walker J, DesRoches CM. Frequency and types of patient-reported errors in electronic health record ambulatory care notes. https://jamanetwork.com/journals/jamanetworkopen/fullarticle/2766834Estiri H, Strasser ZH, Murphy SN. High-throughput phenotyping with temporal sequences. https://academic.oup.com/jamia/article-lookup/doi/10.1093/jamia/ocaa288Geva A, Stedman JP, Manzi SF, Lin C, Savova GK, Avillach P, Mandl KD. Adverse drug event presentation and tracking (ADEPT): semiautomated, high throughput pharmacovigilance using real-world data. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7660953/Zhang Z, Yan C, Mesa DA, Sun J, Malin BA. Ensuring electronic medical record simulation through better training, modeling, and evaluation. https://academic.oup.com/jamia/article/27/1/99/5583723